Situación del personal de Enfermería en el servicio de urgencias en una institución de tercer nivel, en Medellín en 1998 (2000)
ABSTRACT: A descriptive study was undertaken concerning the individual perception of the work which the nursing staff performs in a tertiary care hospital in the city of Medellin. The data was obtained through an inquire which was self-reported by 28 people in which it was investigated by personal characteristics: gender, age, type of contract, day and night hours and breaks during the working day. Personal satisfaction was also asked about which was determined by intrinsic motivation factors such as: amount of work, recognition received for performance, training and orientation. Extrinsic factors were: acceptance of suggestions, facilities, availability of resources and salary. Personal aspects were also taken into account such as stress, the relationship between co-workers, and the influence of work in personal life.